Nomenclatural corrections in vascular plants, 1. Valid publication of Allium savranicum “Besser” - Sennikov, Alexander; Seregin, Alexei (Phytotaxa, 2014)
This paper opens a series of short notes dealing with critical cases in nomenclature of vascular plants. References to the International Code of Nomenclature for algae, fungi and plants (abbreviated as ICN) are provided according to its Melbourne edition (McNeill et al. 2012).